2019
DOI: 10.31458/iejes.423600
|View full text |Cite
|
Sign up to set email alerts
|

4006-TÜBİTAK Bilim Fuarı’na Katılan Ortaokul Öğrencilerinin Bilim Fuarı Hakkındaki Görüşleri

Abstract: Teknolojik aletler kullanarak bilimsel süreç becerilerin yer aldığı bilimsel uygulamalardan birisi de okullarda düzenlenen bilim fuarlarıdır. Bunların en önemlisi de okullara destek veren 4006-TÜBİTAK Bilim Fuarlarıdır. Bu fuarlar sayesinde okullara gerekli destekler sağlanarak bilim fuarları yapılabilmektedir. Bu çalışmanın amacı, 2015-2016 eğitim öğretim yılında 116B906 numaralı 4006-TÜBİTAK Bilim Fuarları'na katılmış öğrencilerin bilim fuarı hakkındaki görüşlerini incelemektir. Araştırmanın nitel araştırma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…In the study, it was concluded that participating in the science fair will contribute to the personality traits of students in different fields, especially in self-confidence and self-expression. Similar results were reported by Avcı and Su Özenir (2018), Çolakoğlu (2018), Sontay, Anar and Karamustafaoğlu (2019). Another result obtained from the study is that participating in the science fair with science projects increases the students' science success and develops positive attitudes and motivations towards science.…”
Section: Finding Discussion and Conclusionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the study, it was concluded that participating in the science fair will contribute to the personality traits of students in different fields, especially in self-confidence and self-expression. Similar results were reported by Avcı and Su Özenir (2018), Çolakoğlu (2018), Sontay, Anar and Karamustafaoğlu (2019). Another result obtained from the study is that participating in the science fair with science projects increases the students' science success and develops positive attitudes and motivations towards science.…”
Section: Finding Discussion and Conclusionsupporting
confidence: 89%
“…Another result obtained from the study is that participating in the science fair with science projects increases the students' science success and develops positive attitudes and motivations towards science. It is reported in studies in the literature that participation in activities such as science fairs, science festivals and project studies improves students' science achievement, attitude and motivation (Camcı, 2008;Deniş-Çeliker and Erduran-Avcı, 2015;Durmaz, et al, 2017;Avcı and Su Özenir, 2018;Sontay, Anar and Karamustafaoğlu, 2019). Therefore, the results obtained from the study are in parallel with the literature.…”
Section: Finding Discussion and Conclusionsupporting
confidence: 74%
See 1 more Smart Citation
“…When the literature is examined, it is seen that the studies on the project preparation process are limited. Sontay, Anar and Karamustafaoğlu, (2019) concluded that during the project preparation process, they learned science subjects, did a literature review for the project, obtained the materials, and received help from parents and friends in this process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is seen that these results are similar to the literature. In the literature, it is seen that scientific activities increase students' attitudes (Akay, 2013;Babaoğlan Özdemir and Babaoğlan, 2019;Camcı, 2008;Durmaz et al, 2017;Fisanick, 2010;Karadeniz and Ata, 2013;Birinci Konur at al., 2011;Sontay et al, 2019;Şahin, 2012;Yıldırım and Şensoy, 2016), improving scientific process skills (Camcı, 2008), and increasing science achievement (Korur et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%